Verification by tests of models proposed for synchronous machines, excitation control systems, water supply and turbines and its control systems for colbún and machicura power plants - Agüero, Jorge Luis (2005)
In this paper several models proposed for Excitation Control Systems, Synchronous Machines, Prime Movers Control System and Turbines corresponding to the Hydraulic power plants of Colbún and Machicura are shown and verified. These power plants are located in the “Interconnected Central System” (SIC), Chile’s largest grid and are part of the Colbún subsystem. This grid subsystem also bears industrial load. It supplies energy to “El Teniente” -world’s largest copper mineand to several paper manufacturing plants. The models were used to study the Colbún subsystem under island operation when the SIC blacks out due to under-frequency conditions.